Assessment of IL_6 and IL_34 Serum in Patients with Diabetic Foot Ulcers - Zghair Hussein, Sarah; H. Al-azzawi, Raghad (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Diabetes foot ulcers (DFUs) are serious vascular pathological effects related to diabetes mellitus. Interleukins are a subclass of cytokines represent a diverse category of signaling particles which adjust cellular activities. Interleukin-6 (IL-6), a central cytokine in acute inflammatory reaction, stimulating liver to produce acute phase proteins and contributing to the progress of diabetes. Recently, recognized pro-inflammatory cytokine interleukin-34 (IL)-34 binds to colony stimulating factor-1(CSF-1) receptor and is implicated in pathogenesis of different chronic inflammatory and autoimmune conditions. This study aimed to estimate serum concentrations of IL-6 and IL-34 in diabetic individuals with DFUs compared to healthy controls. The research, conducted from January to July 2022 at Al-Hussein Teaching Hospital in Samawa/Iraq, Medical city/Baghdad Hospital in Baghdad/ Iraq. The study was conducted on two groups: 140 DFUs patients and 70 control group. The age range of DFUs patients was 29–87 years, whereas of control group was 18–57 years. The levels of serum IL-6 and IL-34 were evaluation using sandwich ELISA technique. The average random blood sugar level in patients was 226.9 mg/dL. The findings shown that DFUs were significantly associated with factors (P value ˂ 0.05) were: 93(66.4%) are male, high 79(56.40%) are within (31-60) year, smoking 50 (35.7%), overweight 55 (39.3%), type 2 DM 131(93.6%). Similarly, results revealed a significant elevation in IL-6 and IL-34 levels in DEUs individuals compared to control group (P ≤ 0.05).